Interactions between West Nile Virus and the microbiota of Culex pipiens vectors: a literature review - Garrigós, Marta (2023)
The flavivirus West Nile virus (WNV) naturally circulates between mosquitoes and birds, potentially affecting humans and horses. Different species of mosquitoes play a role as vectors of WNV, with those of the Culex pipiens complex being particularly crucial for its circulation. Different biotic and abiotic factors determine the capacity of mosquitoes for pathogen transmission, with the mosquito gut microbiota being recognized as an important one. Here, we review the published studies on the interactions between the microbiota of the Culex pipiens complex and WNV infections in mosquitoes. Most articles published so far studied the interactions between bacteria of the genus Wolbachia and WNV infections, obtaining variable results regarding the directionality of this relationship. In contrast, only a few studies investigate the role of the whole microbiome or other bacterial taxa in WNV infections. These studies suggest that bacteria of the genera Serratia and Enterobacter may enhance WNV development. Thus, due to the relevance of WNV in human and animal health and the important role of mosquitoes of the Cx. pipiens complex in its transmission, more research is needed to unravel the role of mosquito microbiota and those factors affecting this microbiota on pathogen epidemiology. In this respect, we finally propose future lines of research lines on this topic.